THE STUDENTS' ABILITY IN LEARNING TREE DIAGRAMS AT THE FIFTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - Desi Rahmilia; Edi Ardian; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study is to assess students' ability to learn tree diagrams in the fifth semester of the English Study Program at the Islamic University of Indragiri. This type of research is descriptive and quantitative. The population of this research is the fifth-semester students of the English Education Study Program at the Islamic University of Indragiri. This study's population and samples totaled 13 people, drawn using a total sampling technique. The researcher used a test as an instrument to assess the student's ability to learn tree diagrams. For data analysis, researchers used statistical analysis to determine test results. The test results show that the fifth semester students of the English Study Program at the Islamic University of Indragiri have adequate ability in learning tree diagrams, with an average of 59.2. The researcher concludes that the fifth semester students of the English Study Program at the Islamic University of Indragiri should improve their ability to learn tree diagrams.